Peningkatan Hasil Belajar Mengubah Pecahan Biasa Dan Campuran Ke Pecahan Desimal Dengan Menggunakan Model Kooperatif Learning Tipe STAD Di Kelas IV SDN 28 Batipuah Ateh Kabupaten Tanah Datar - Gitasari, Desrina; Ahmad, Syafri; Mayarnimar, Mayarnimar (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2021)
This research is motivated by the low learning outcomes of students in learning to change ordinary and mixed fractions to decimal fractions. The teacher usually directly gives examples of questions that are formally solved and then proceed with the giving of exercises. So students are not motivated and are not interested in understanding the learning. The purpose of this research is to describe Mathematics learning by using the STAD Cooperative Learning model to improve student learning outcomes in class IV SDN 28 Batipuah Ateh Tanah Datar District.           The approach used in this study is a qualitative and quantitative approach. This type of research is Classroom Action Research (CAR). This research includes: 1) Planning, 2) Implementation, 3) Observation and 4) Reflection. Which consists of two cycles, namely in one cycle two meetings. Data collection techniques in this study were observation and tests, while the research instruments were observation sheets and tests in the form of objective questions and descriptions. And the subjects in this study were students of grade IV SDN 28 Batipuah Ateh Tanah Datar District.            The results of this study are: a) Observation of RPP in the first cycle with a score of 80% and the second cycle with a score of 90%. b) The results of observations of teacher activity in the first cycle with a score of 85% and the second cycle with a score of 94% and on the aspects of students in the first cycle 82% and in the second cycle with a score of 94%. c) Learning outcomes of students in cycle I on cognitive, affective and psychomotor aspects with an average of 73 and on cycle II with an average of 83. From the results of the research conducted it can be concluded that by using the STAD type cooperative learning model can increase activities and results student learning in learning mathematics in class IV SDN 28 Batipuah Ateh Tanah Datar District.